Adherence to the new WCRF cancer prevention recommendations associates with a decreased cancer risk. (30th September 2020) - Deschasaux, M; Bourhis, L; Chazelas, E; Debras, C; Hercberg, S; Latino-Martel, P; Julia, C; Kesse-Guyot, E; Srour, B; Touvier, M
Abstract: Background: Cancer remains one of the leading causes of death worldwide. In 2018, following its summary report, the World Cancer Research Fund (WCRF) issued its recommendations for cancer prevention based on the nutritional risk factors with a sufficient level of evidence. Our objective was to study whether adherence to these new recommendations leads to a reduced risk of cancer. Methods: This study included 80, 604 participants from the NutriNet-Santé population-based cohort study (2009-2019). Adherence to the 2018 WCRF recommendations was assessed using the operationalized score on a 7-point scale, proposed by Shams-White et al (Nutrients 2019), including: weight, physical activity, fruit and vegetables, dietary fibers, ultra-processed foods, red and processed meat, sugary drinks and alcohol. Usual dietary intakes were assessed using repeated 24h-dietary records and physical activity level using the IPAQ questionnaire. Multi-adjusted Cox proportional hazard models were used for the analyses. Results: A total of 2, 438 incident cancer cases were diagnosed during follow-up (median: 7.4 years). The median WCRF 2018 adherence score was 3.75 (IQR: 3.25-4.50). An increase of 1-point increment in the score was associated with a decreased risk of cancer overall (HR = 0.90; 95%CI 0.86-0.90; P<.0001), and of obesity-related cancers (n = 1549 cases, HR = 0.89; 0.84-0.94; P<.0001), aerodigestive cancers (n = 390, HR = 0.83; 0.74-0.93; P = 0.001), breast cancer (n = 749, HR = 0.92; 0.85-1.00; P = 0.04) and a non-significant trends for prostate (n = 332, HR = 0.89; 0.79-1.01; P = 0.07) and colorectal (n = 218, HR = 0.88; 0.76-1.03; P = 0.1) cancers. Conclusions: Our results suggest that a higher adherence to the WCRF 2018 recommendations for cancer prevention is associated to a decreased risk of cancer. Given the consistency between overall food-based dietary guidelines and the WCRF cancer recommendations, our result support their general promotion to the general public and transposition as public health actions. Key messages: Following the recommendations for cancer prevention issued by the WCRF in 2018 can contribute to decrease the burden of cancer. The WCRF cancer recommendations are consistent with overall food-based dietary guidelines and should be promoted to the general public and transposed as public health actions.